Acute Stress Response in Women with Recurrent Miscarriage and Infertility - Bhandari, Sunita (Nepalese Medical Journal, 2018)
Introduction: Stress has been linked to reproductive failure which includes miscarriage and Infertility. Several studies showed high levels of psychological stress and stress biomarkers in women with reproductive failure. However, very few studies are done to measure the stress response. So the current study sought to assess whether women with reproductive failure have exaggerated acute stress response. Materials and Methods: This was a cross-sectional comparative study. Blood samples were collected immediately after venipuncture, and again 20 min later from 15 fertile controls, 20 recurrent miscarriage patients, and 40 infertile patients to measure natural killer cells and cortisol levels. Results: The percentage of peripheral blood NK cells (total CD3-CD56+) and serum total cortisol level did not change significantly across the two samples of immediately after venipuncture, and again 20 min later in the fertile controls (p=0.358,and p=0.890 respectively). However, there was a significant decline in the second sample in women with Infertility (p<0.05 for serum cortisol and p<0.05 for NK cell) and with recurrent miscarriage (p<0.05 for serum cortisol). There was a decline of NK cell in the 2nd sample in women with recurrent miscarriage though not to significant level (P>0.05). Conclusions: Women with recurrent miscarriage and Infertility may be more vulnerable to acute stressor. Nepalese Medical Journal, vol.1, No. 1, 2018, Page: 17-20